(untitled) (Simbiótica. Revista Eletrônica, 2022)
In this reflexive exercise we (re)visit some ethnographic data which resulted in a master´s dissertation drawing from fieldwork conducted among the Kaiowa and the Guarani, including some experiences and experimentations the authors have gone through along their different trajectories in research and teaching at a Federal University located in the city of Dourados – MS. From a transdisciplinary viewpoint, we have sought to think over the ontologies and itineraries that make up Indigenous Health in Dourados, drawing from both the different itinerations of the indigenous individuals e communities around the Unified Health System (SUS), and from our experiences and trajectories as professionals working on Primary Care and/or researchers who work with the indigenous communities in the area. Into the picture, there are ways of conceiving Health that rhyme with struggle, land, pray, collectivity, alliances, bodies, humans and non-humans and eternally walking. Keyword: health; itinerations; Kaiowá and Guarani; Dourados – MS.